Gaining and sustaining competitive advantage - Barney, Jay B. (Addison-Wesley Pub. Co., 1997)
Dealing with competitive advantage in business, this work develops a framework that emphasizes the importance of understanding not only the threats and opportunities in a firm's competitive environment, but also the implications of firms' organizational strengths and weaknesses.